Aloe – a unique source of biologically active compounds - Garkava, K. G.; Ukrainska, A. O.; Chaika, D. A. (Problems of Environmental Biotechnology, 2020)
The review of various aloe species as potent source of biologically active compounds is presented. The general description of aloe species their morphology and characteristic features is presented. Various biologically active compounds that may be derived from aloe species are described. The ways of application of biologically active compounds as potential therapeutic agents and as additives to drugs or cosmetics have been analyzed.